Synthesis of nanostructured powders and thin films of iron sulfide from molecular precursors. Issue 51 (15th August 2018) - Almanqur, Laila; Vitorica-yrezabal, Inigo; Whitehead, George; Lewis, David J.; O'Brien, Paul
Abstract : Iron(iii ) xanthate single-source precursors were used to deposit iron sulfide thin films and nanostructures by spin coating and solid state deposition. Abstract : Iron(iii ) xanthate single-source precursors [Fe(S2 COR)3 ] (R = methyl, ethyl, isopropyl and 1-propyl) were used to deposit iron sulfide thin films and nanostructures by two simple, efficient and low-cost methods (spin coating and solid state deposition). The single-crystal X-ray structures of the iron(iii ) n -propyl xanthate and iron(iii ) iso-propyl xanthate have been determined. Thermogravimetric analysis (TGA) studies of the complexes shows that decomposition of the complexes produces iron sulfide, pyrite or trolite. The crystallinity of iron sulfide thin films and powder samples was studied using X-ray diffraction (XRD), and their morphology was studied by scanning electron microscopy (SEM).